Chinese grammar at work - Huang, Xuanfan (Studies in Chinese language and discourse, 2013)
Chinese Grammar at Work adopts a cognitive-functional approach and uses a corpus-based methodology to examine how Chinese syntax emerges from natural discourse context and what the evolving grammar at work looks like. In this volume the author weaves together an array of fresh perspectives on clause structure, constructions, interactional linguistics, cognitive science and complex dynamic systems to construct a grammar of spoken Chinese. The volume contains discussions of a large number of topics: contiguity relation, the roles of repair strategies in the shaping of constituent structur.